Penguatan Konsep Literasi Matematika Bagi Siswa Smp Negeri 8 Kota Kupang - Pangaribuan, Rapmaida M.; ., Ariyanto; Ndii, Meksianis Z. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2023)
Asesmen Kompetensi Minimum (AKM) is one of the assessment instruments of the Asesmen Nasional (AN). There are two main competencies that are measured in the AKM, namely reading literacy and mathematical literacy (numeracy). The AN results in 2021 show that 2 out of 3 students have not achieved the minimum numeracy competency. One of the factors causing this is students’ lack of motivation in learning numeracy. Many students find numeracy difficult to understand and very scary, uninteresting because there are many symbols and formulas. The purpose of this community service activity is to increase students' motivation in learning numeracy. The implementation of activities in the form of training and assistance to strengthening the concept of mathematical literacy. The participants in this activity were 57 students of SMP Negeri 8 Kota Kupang. The results of the activity evaluation showed that students' interest and understanding of mathematical literacy (numeration) had changed positively and students' motivation to learn numeracy had increased.